A reaction–diffusion kinetic model for the heterogeneous N-deacetylation step in chitin material conversion to chitosan in catalytic alkaline solutions. Issue 6 (17th October 2018) - Bradić, Bojana; Bajec, David; Pohar, Andrej; Novak, Uroš; Likozar, Blaž
Abstract : New mechanistic insight into the modelling of the heterogeneous N-deacetylation step of α-chitin, obtained from waste crustacean shells. Abstract : This conversion study provides a new mechanistic insight into the modelling of the heterogeneous N-deacetylation step of α-chitin, obtained from waste crustacean shells, using a catalytic alkaline solution at different operating temperatures (25–80 °C) and concentrations (50–80 wt%). Transient particle-size distributions for two separate experiments with smaller powder or larger flake morphologies were obtained by applying an inline tracking system. The degree of deacetylation (DDA), polymer molecular mass and viscosity of the deacetylated raw resource were continuously monitored with time until the maximum DDA was reached. The mechanism of the conversion of an average biopolymer chain was described with a reaction–diffusion kinetic model, solved for all fraction intervals, and optimised. The effective diffusivity coefficient was estimated with regression analysis; the geometry of the particles was approximated as having spherical dimensions, and material isotropy was presumed. A second-order reaction process took place, since the content of the dissolved hydroxyl ions inside the pores was not considered constant. Additionally, several analytical tools such as scanning electron microscopy (SEM) was employed as well as specific porosity measurements to get a deeper phenomenological understanding of the material's morphological transformation. The selected mathematical relationship granted a relatively good agreement for the cumulative experimental data by regarding the kinetics in the initial consumption phase, as well as the subsequent transport resistance for OH − . The developed descriptive approach, together with online measuring methods, could enable a more comprehensive option for commercial productivity increase, as well as unit operations scale-up.